Physical Activity in the Prevention and Treatment of Stroke. (1st October 2011) - Gallanagh, Siobhan; Quinn, Terry J.; Alexander, Jen; Walters, Matthew R.
Abstract : The role of physical activity in the prevention of stroke is of great interest due to the high mortality and significant impact of stroke-related morbidity on the individual and on healthcare resources. The use of physical activity as a therapeutic strategy to maximise functional recovery in the rehabilitation of stroke survivors has a growing evidence base. This narrative review examines the existing literature surrounding the use of exercise and physical therapy in the primary and secondary prevention of stroke. It explores the effect of gender, exercise intensities and the duration of observed benefit. It details the most recent evidence for physical activity in improving functional outcome in stroke patients. The review summaries the current guidelines and recommendations for exercise therapy and highlights areas in which further research and investigation would be useful to determine optimal exercise prescription for effective prevention and rehabilitation in stroke.